KODE ETIK PUSTAKAWAN: HUBUNGAN PUSTAKAWAN DENGAN MASYARAKAT DI DINAS PERPUSTAKAAN DAN KE.ARSIPAN KOTA MEDAN - ., Nur’aini; Nasution, Laila Hadri (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This research took place at the Medan City Archives and Library Service. The purpose of this study was to determine the relationship between li- brarians and the community at the Medan City Archives and Library Service. This type of research uses qualitative methods with a descriptive approach. Data collection methods used were observation, documenta- tion and interviews. The results of this study indicate that the relationship between the librarian and the community in the Department of Library and Archives of Medan City has been implemented well. Librarians carry out their duties and responsibilities as best as possible to the people who come or visit the Medan City Archives and Library Service. This research is an input for all librarians to have good ethics in carrying out their profession as librarian.